2018
DOI: 10.1111/oik.04978
|View full text |Cite
|
Sign up to set email alerts
|

Context‐dependency and anthropogenic effects on individual plant–frugivore networks

Abstract: Anthropogenic activities, such as grazing by domestic animals, are considered drivers of environmental changes that may influence the structure of interaction networks. The study of individual‐based networks allows testing how species‐level interaction patterns emerge from the pooled interaction modes of individuals within populations. Exponential random graph models (ERGMs) examine the global structure of networks by allowing the inclusion of specific node (i.e. interacting partners) properties as explanatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 85 publications
3
47
0
2
Order By: Relevance
“…This could explain the increased quantity component and interaction strength in both antagonist and mutualists interactions in this grazed area. These compensatory trends are analogous to those recently reported by Miguel et al (2018) comparing grazed versus ungrazed habitats; they found that frugivores visit fewer trees in more structurally-complex habitats compared with trees in a more disturbed and physiognomically-simplified habitat.…”
Section: Frugivore Visitors and Seed Dispersal Effectivenesssupporting
confidence: 87%
“…This could explain the increased quantity component and interaction strength in both antagonist and mutualists interactions in this grazed area. These compensatory trends are analogous to those recently reported by Miguel et al (2018) comparing grazed versus ungrazed habitats; they found that frugivores visit fewer trees in more structurally-complex habitats compared with trees in a more disturbed and physiognomically-simplified habitat.…”
Section: Frugivore Visitors and Seed Dispersal Effectivenesssupporting
confidence: 87%
“…In plant dispersal networks, diaspores produced by the parent plant can be dispersed through endozoochory by different co-occurring vectors. These networks have been established principally for frugivory and endozoochory (Dugger et al, 2018;Miguel et al, 2018). Fedriani and Delibes (2009) studied the role of different mammals (e.g., wild pig; red deer; badger, Meles meles and red fox, Vulpes vulpes) dispersing the Iberian pear (Pyrus bourgaeana).…”
Section: Overlap and Complementarity Of Ungulate-mediated Dispersalmentioning
confidence: 99%
“…Graomys griseoflavus , Akodon dolores , Eligmodontia typus , Calomys musculinus and Microcavia maenas ) practice food hoarding, making both larder-hoards and scatter-hoards with different effects on seed survival (Campos et al, 2007, 2017; Giannoni et al, 2013). In this relationship among P. flexuosa and its assemblage of dispersers, previous studies have shown that quantitative aspects of SDE directly related to animal visits and fruit removal are affected by changes in habitat heterogeneity under different land uses (Campos et al, 2016; Bessega et al, 2017; Tabeni et al, 2017; Miguel et al, 2017, 2018a,b). Although the development of the SDE model for P. flexuosa began years ago, using an approach that combines field and laboratory experiments, the aim of the present study is to provide data to fill in some gaps in the model.…”
Section: Introductionmentioning
confidence: 97%